Hubungan tinggi badan terhadap jarak jauh lompatan pada saat melakukan lompat jauh siswa laki-laki SMAN Pakusari di kelas X4 - Gita Karinda; Ahmad Sulaiman; Topo Yono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of height on long jump results in the sport of long jump. The study uses a quantitative method with a correlational approach. The sample consisted of 20 students selected using purposive sampling from a population of 45 students. Data were obtained through direct measurement of height using a measuring device (CM) and jump results using a standard measuring device (M). Data analysis was performed using SPSS version 25, including Pearson's correlation test, t-test, F-test, and simple linear regression. The results showed a correlation value of r = 0.599 with a significance of 0.005 < 0.05, which means that there is a positive and significant relationship between height and long jump results. The t-value = -42.032 with Sig. = 0.000 indicates that height has a significant partial effect on long jump results, while the F-test result of 68.230.496 with Sig. = 0.000 indicates that the regression model is simultaneously significant. Thus, it can be concluded that height has a significant effect on long jump distance in the sport of long jump. Kata Kunci: Athletics, height, long jump, anthropometry